Creating E-Catalogue Flipbook Based as Advertising Media at PT Vestindo Sukses Indonesia in Malang - Ayu Farah Fediasha; Tri Ramadani Arjo; Fatkhur Rochman (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
PT Vestindo Sukses Indonesia is a Malang-based manufacturer of ice machines and ice crystals. Observations show that its current digital advertising media—Instagram and the official website—are less effective due to limited information and the absence of interactive visual elements. To address this, a flipbook-based e-catalogue was developed as an interactive and informative digital marketing tool. This study aims to evaluate its effectiveness using action research, with data collected through interviews, observations, and questionnaires involving 16 respondents, including owners, employees, marketing experts, computer experts, and company agents. The design was assessed using the EPIC model (Empathy, Persuasion, Impact, Communication). Results indicate a high effectiveness score, with an average EPIC Rate of 4.7. The highest score in the persuasion indicator shows that the flipbook successfully influenced audience interest. Its attractive visuals, easy access, and comprehensive information make it a viable medium to enhance the company’s promotional strategy, increase consumer engagement, and encourage deeper understanding of the products. The final flipbook e-catalogue can be accessed at: https://heyzine.com/flip-book/ce3411e190.html.